Organizing Culture Scale For PMF From Physical Educators’ Point Of View - Hasoon, Mustafa; Abduljabar, Farqad (Journal of Physical Education, 2020)
The aim of the research is to design organizational culture for physical educators and military training staff for PMF as well as identifying the level of organizational culture in popular mobilization forces PMF. The researcher used the descriptive method on (300) physical educators of PMF. Ten physical educators as well as 10 officers were selected for the pilot study. The researcher suggested (25) items for this scale to collect the data and come up with the conclusions. The results showed that origination is a vital means for making a difference in the PMF performance.